Alat Permainan Edukatif Golf Anak Usia Dini sebagai Program Edupreneur Prodi Pendidikan Islam Anak Usia Dini - Leli Fertiliana Dea; Yusuf, M.; Saidun Anwar, M.; Choirudin, Choirudin; Ayu Juniati, Dwi (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
The mismatch between competence and job requirements is a cause of rampant unemployment. Moreover, the imbalance between supply and demand, as well as the quality of human resources are produced. The edupreneur program in the Islamic Early Childhood Education (IECE) department can equip graduates to be more competitive, especially looking for competent jobs. This study aims to develop an Educational Game Tool (EGT) in the form of APE Golf as a form of entrepreneurial education program (edupreneur) in the IECE study program. The method used is research and development (research and development) Borg and Gall. EGT Golf development is carried out in several stages, namely: the initial trial design stage given to material expert validators and media experts and the main field trial stage with 14 children. The results of this study indicate that EGT golf is feasible to be used as an educational program for students and prospective teachers in the IECE department. EGT golf testing with respondents can encourage student activity and develop fine and gross motor skills. EGT golf can also be used as a learning medium in early childhood education.